One Street Away - Institute for Societal Leadership, (Institutional Knowledge at Singapore Management University, 2015)
According to Dr Goh Wei-Leong, Founder and Chairman of Singapore-based social impact organisation HealthServe, the average migrant worker would have paid an agent from between $5,000 and $12,000 Singapore dollars to come to Singapore for work which barely gives him $20 a day. Beyond the low wages, migrant workers in Singapore do face a myriad of problems that range from salary disputes and workplace-related injuries to discrimination and loneliness. In this documentary, watch how Dr Goh strives to build a home away from home for men he considers unsung heroes who are working hard to build the pillars of our society.